(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of positive Troponin I in non-acute coronary syndrome critically ill patients, at a tertiary care hospital, Karachi. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Cardiology Unit at Liaquat National Hospital Karachi from June 2019 to Dec 2019. Materials and Methods: Total 148 patients of either gender with age between 35 to 70 years, diagnosed as critical illness were included. Non-ACS was diagnosed through ECG and echocardiography findings. Blood sample was taken for a troponin I test. Outcome variable was diagnosis of elevated Troponin I level. SPSS version 21 used for data analysis. Mean±SD were calculated for quantitative variables. Qualitative variables presented as frequency and percentages. Chi square test was applied and p-value ≤0.05 was taken as significance. Results: There were 111 male and 37 female patients. The mean age was 51.15±9.76 years. The mean troponin-I score was 3.08±7.47 ng/mL with range 50.7(0.3–51.0). The elevated troponin-I was observed in 84(56.8%) patients. The result showed that age was significantly association with elevated troponin but gender, duration of illness, hypertension, and smoking status were not significantly association. Conclusion: In conclusion there was high prevalence of cardiac troponin-positive patients admitted with critical illness other than ACS. It increases with the increase in age, predominant in male gender but no significant association with risk factors was noted.